2017
DOI: 10.5152/tjg.2017.16713
|View full text |Cite
|
Sign up to set email alerts
|

Radical resection of the pancreas should not always be necessary in the surgical management of pancreatic solid pseudopapillary tumor in children

Abstract: Background/Aims: Pancreatic solid pseudopapillary tumor (SPT) is a rare neoplasm in children. In this study, we aimed to present our surgical strategy based on minimal resection by enucleation or limited resection in localized pancreatic SPT. Materials and Methods: We retrospectively analyzed the medical records of children who underwent surgical resection between October 2011 and September 2016. Results: Five female patients with a median age of 15 years (range, 14-17 years) were operated. Tumors were located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…In Tables 3 and 4 we summarize the main characteristics of the studies that focused on long-term outcome of pancreatic functions following oncological surgery in children[ 26 - 37 ]. The data showed that the prevalence of exocrine insufficiency in pediatric patients ranged from 0%[ 29 ] to 83.3%[ 33 ]. Vasudevan et al [ 27 ] found exocrine failure rate similar to our finding (23%), while Cheng et al [ 26 ] found a much lower rate (8.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tables 3 and 4 we summarize the main characteristics of the studies that focused on long-term outcome of pancreatic functions following oncological surgery in children[ 26 - 37 ]. The data showed that the prevalence of exocrine insufficiency in pediatric patients ranged from 0%[ 29 ] to 83.3%[ 33 ]. Vasudevan et al [ 27 ] found exocrine failure rate similar to our finding (23%), while Cheng et al [ 26 ] found a much lower rate (8.6%).…”
Section: Discussionmentioning
confidence: 99%
“…We found endocrine failure in 12.5% and Vasudevan et al [ 27 ] found endocrine failure in 3%. No patients with endocrine insufficiency were found in seven surveys[ 28 , 29 , 31 , 33 , 35 - 37 ]. Cheng et al [ 26 ] reported that only one patient developed endocrine insufficiency in 104 and Park et al [ 34 ] found one in 8 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In children, surgical resections should be as conservative as possible. Instead of radical resections such as pancreaticoduodenoctomy or distal pancreatectomy with splenectomy, enucleation or limited pancreatic resection with negative surgical margins are advocated . In children, it is especially important to recognize this entity because tumour resection can be performed without large safety margins and to avoid long‐term complications, the preservation of pancreatic tissue and spleen should be attempted .…”
Section: Discussionmentioning
confidence: 99%
“…In case of diagnostic uncertainty, EUSguided fine needle aspiration is recommended, which plays an important role in providing accurate and reliable preoperative cytological diagnosis (61,62,63). Papavramidis and Papavramidis (49) include CT-guided FNA in the SPN diagnostic algorithm.…”
Section: Magnetic Resonance Imaging (Mri) Is the Diagnostic Methods Ofmentioning
confidence: 99%